Building an underground nuclear power plant in Singapore - geological and geotechnical considerations - Yong, Shin Mun. (2011)
With the escalating demand for energy in Singapore, constructing a Nuclear Power Plant (NPP) seems an attractive alternative to fossil fuels which are depleting and increasing in cost. However, constraints such as a small land area, vulnerability to terrorist attacks, disposal of radioactive nuclear waste material and possible contamination of the surroundings, call for an underground location for the NPP. There are different types of underground sitings a NPP can adopt. These include level, single and stacked orientations. Phase2, a 2-dimensional plastic finite element program for calculating stresses and displacements around underground openings, is used to provide analysis of potential civil engineering problems present in the layouts proposed.